Analysis of Knowledge and Mother's Ability in Stimulating the Development of Children Aged 18-23 Months - Indarwati, Nanik; Chandra Wahyuni (Journal of Global Research in Public Health, 2016)
Most parents see development from what is visible, so they often ignore developments that are not visible, such as social development of independence so that delays are often not realized if parents' knowledge is low about child development. This study aims to determine the relationship between maternal knowledge about child development stimulation and development stimulation abilities. Using a correlation analytic design with a cross-sectional approach. The population in this study were all mothers who took care of their own children aged 18-23 months in Bandung Village, Gedeg District, Mojokerto Regency in February 2016, with a purposive sampling technique and 35 respondents were obtained. Data collection used questionnaires and checklists. Data analysis used the Spearman Rho Test. The results showed that most respondents had sufficient knowledge about child development stimulation (51.4%) and almost half of respondents had moderate stimulation abilities (45.7%). There is a relationship between knowledge and mother's ability in stimulating child development aged 18-23 years in Bandung Village, Gedeg District, Mojokerto Regency, as evidenced by the results of the Spearman Rho Test, p value = 0.000 or <0.05 so that H1 isaccepted. The better the mother's knowledge about child development stimulation, the higher the mother's ability to carry out stimulation,because the basis of individual behavior is knowledge. Mothers are expected to seek as much information as possible about childdevelopment stimulation and learn how to apply it to children.